In focus : strategies for academic writers - Shulman, Myra. (United states of America University of Michigan Press, 2005)
"In Focus: Strategies for Academic Writers is a concise guide for effective academic writing for native and nonnative speakers. It teaches common academic writing tasks such as paragraphs, summaries, short essays, critical reviews, syntheses, argumentative essays, research papers, and response writing."--BOOK JACKET.
Ch. 1. The focused writer -- Ch. 2. The power writing process -- Ch. 3. Writer's block -- Ch. 4. Skillful proofreading and editing -- Ch. 5. Effective style -- Ch. 6. The cohesive paragraph -- Ch. 7. The accurate summary -- Ch. 8. The logical essay -- Ch. 9. The objective critical review -- Ch. 10. The balanced synthesis -- Ch. 11. The persuasive argument -- Ch. 12. The scholarly research paper -- Ch. 13. Your authentic voice -- App. A. Definitions of writing terms -- App. B. Examples of writing styles -- App. C. Sentence connectors -- App. D. The power writing process -- App. E. Writing evaluation forms -- App. F. Internet research -- App. G. "My healthy lifestyle" revision (pages 49-50).
"The FOCUS Approach (Format-Organization-Content-Understanding-Style) helps students analyze the writing task at hand and clarify the goals of their projects, while the POWER Writing Process (Prepare-Outline-Write-Edit-Rewrite) allows students to complete the writing and revision of their assignments one step at a time"--P. [4] of cover.
Includes bibliographical references.
Keywords: Dissertations, Academic -- Authorship; English language -- Rhetoric; Academic writing; English language -- Rhetoric -- Problems, exercises, etc; Academic writing -- Problems, exercises, etc